The role of neoantigens in response to immune checkpoint blockade - Riaz, Nadeem (Int Immunol, 2016)
Immune checkpoint blockade has demonstrated substantial promise for the treatment of several advanced malignancies. These agents activate the immune system to attack tumor cells. For example, agents targeting CTLA4 and programmed cell death 1 (PD-1) have resulted in impressive response rates and, in some cases, durable remissions. Neoantigens are mutations that encode immunologically active proteins that can cause the immune system to recognize the affected cell as foreign. Recent data have made it clear that these mutations are, in large part, the functional targets of immune checkpoint blockade. This review summarizes the key discoveries leading up to this important conclusion and discusses possible applications of neoantigens in cancer therapy.